Biphenyl hydrogenation over supported transition metal catalysts under supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, C. V.; Sato, O.; Shirai, M. (Applied Catalysis A - General, 2005)
Catalytic hydrogenation of biphenyl to bicyclohexyl, an organic hydrogen storage medium, was examined over supported transition metal catalysts in supercritical carbon dioxide solvent. The yield of bicyclohexyl was almost 100% over the charcoal-supported rhodium (Rh/C) and ruthenium (Ru/C) catalysts at the temperature of 323 K, which was much lower than that required for biphenyl hydrogenation in organic solvents (573 K). The initial activity was higher over the Rh/C catalyst, while the initial selectivity to bicyclohexyl was higher over the Ru/C catalyst. The conversion of biphenyl increased with increase in hydrogen and carbon dioxide pressures, while the selectivity to bicyclohexyl was independent of hydrogen and carbon dioxide pressures over both catalysts. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: bicyclohexyl; biphenyl; charcoal-supported rhodium catalyst; charcoal-supported ruthenium catalyst; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide

Enhanced selectivity to decalin in naphthalene hydrogenation under supercritical carbon dioxide - Hiyoshi, Norihito; Miura, R.; Rode, C. V.; Sato, O.; Shirai, M. (Chemistry Letters, 2005)
A charcoal-supported rhodium catalyst was highly active and selective to decalin for the hydrogenation of naphthalene at very low temperature (333 K) under supercritical carbon dioxide.

Control of stereoselectivity in 4-tert-butylphenol hydrogenation over a carbon-supported rhodium catalyst by carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Ebina, Takeo; Shirai, Masayuki (Chemistry Letters, 2006)
cis-4-tert-Butylcyclohexanol was obtained with a high cis ratio (cis/(cis + trans) = 0.9) in the hydrogenation of 4-tert-butylphenol over a carbon-supported rhodium catalyst along with hydrochloric acid in supercritical carbon dioxide solvent.

Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin

Ring hydrogenation of naphthalene and 1-naphthol over supported metal catalysts in supercritical carbon dioxide solvent - Shirai, M.; Rode, C. V.; Mine, Eiichi; Sasaki, A.; Sato, O.; Hiyoshi, Norihito (Catalysis Today, 2006)
Catalytic ring hydrogenations of naphthalene and 1-naphthol were studied over several supported metal catalysts in supercritical carbon dioxide solvent at low temperature. Higher concentration of hydrogen in supercritical carbon dioxide and lower reaction temperature were responsible for higher catalyst activity and selectivities to the desired partial ring hydrogenated products as compared with those observed in organic solvent for the same catalyst. (c) 2006 Elsevier B.V. All rights reserved.
8th International Conference on Carbon Dioxide Utilization, Univ Oslo, Oslo, NORWAY, JUN 20-23, 2005
Keywords: 1-naphthol; Hydrogenation; Naphthalene; Supercritical carbon dioxide; supported metal catalyst

Selective hydrogenation of naphthols to tetralones over supported palladium catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2006)
Naphthols were selectively hydrogenated to the corresponding tetralones over supported palladium metal catalysts in super-critical carbon dioxide solvent.

Stereoselective hydrogenation of tert-butylphenols over charcoal-supported rhodium catalyst in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, Chandrashekhar V.; Sato, Osamu; Tetsuka, Hiroyuki; Shirai, Masayuki (Journal of Catalysis, 2007)
Hydrogenation of 2-, 3-, and 4-tert-butylphenols was studied over a charcoal- supported rhodium catalyst in supercritical carbon dioxide (scCO(2)) solvent, and the results were compared with those in organic solvents. In the hydrogenation of 4-tert-butylphenol, a higher cis ratio for 4-tert-butylcyclohexanol (0.79) was obtained in scCO(2) (10 MPa) than in 2-propanol (0.70) and cyclohexane (0.64) under similar conditions of hydrogen pressure (2 MPa) and temperature (313 K). In the case of 2-tert-butylphenol, the cis ratio for 2-tert-butylcyclohexanol was as high as 0.95 in both scCO(2) and 2-propanol (hydrogen pressure, 2 MPa; reaction temperature, 313 K). In the case of hydrogenation of 3-tert-butylphenol, the cis ratio decreased with the progression of consecutive hydrogenation of 3-tert-butylcyclohexanone intermediate. In addition, the stereoselectivity to cis-tert-butylcyclohexanols in scCO(2) was improved in the presence of hydrochloric acid. It was found that the protons of hydrochloric acid accelerated the hydrogenation of the intermediates, tert-butylcyclohexanones, to the corresponding cis-tert-butylcyclohexanols. The hydrogenation mechanism of tert-butylphenols, particularly the enhanced selectivity to cis-tert-butylcyclohexanols in scCO(2), is postulated based on the observed reaction profiles. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: charcoal-supported rhodium catalyst; stereoselective hydrogenation; supercritical carbon dioxide solvent; tert-butylcyclohexanol

Enhancement of glycerol conversion to acetol in high-temperature liquid water by high-pressure carbon dioxide - Yamaguchi, Aritomo; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2008)
Dehydration of glycerol to acetol proceeded in high-temperature liquid water at 573 K in a batch reactor. The acetol formation rate increased with an addition of high-pressure carbon dioxide.

Activity and selectivity behavior of 1,2-epoxyethylbenzne hydrogenation in carbon dioxide solvent - Rode, Chandrashekhar V.; Hiyoshi, Norihito; Mine, Eiichi; Shirai, Masayuki (Industrial & Engineering Chemistry Research, 2009)
Catalytic hydrogenation of 1,2-epoxyethylbenzene to 2-phenylethanol over charcoal-supported noble metal in carbon dioxide was studied, and the results were compared with those in heptane and methanol. Charcoal-supported palladium and platinum (Pd/C and Pt/C) catalysts were active metal species for the hydrogenation in solvents. The order of activities over palladium and platinum was heptane < carbon dioxide < methanol; however, the formation of dehydroxylated byproduct was suppressed in carbon dioxide solvent. Negative carbon dioxide pressure effect was observed over the Pd/C and Pt/C catalysts in the carbon dioxide solvent.

Phase behavior of hydrogenation of 2-tert-butylphenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent - Hiyoshi, Norihito; Masuda, Yoshio; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of Chemical and Engineering Data, 2009)
Catalytic hydrogenation of 2-tert-butyl phenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent at 313 K was studied in a batch reactor. To elucidate the effect of carbon dioxide pressure on the initial rate of reaction, the phase behavior of the ternary (2-tert-butylphenol-carbon dioxide-hydrogen) system was separately observed with a view cell, and the calculations of vapor-liquid equilibrium and compositions in the vapor and liquid phases inside the reactor were carried out using the Peng-Robinson equation of state. The hydrogenation behavior in the carbon dioxide solvent is discussed based on the phase behavior of the ternary system.

Kinetic analysis of 4-isopropylphenol hydrogenation over activated carbon-supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Green Chemistry, 2012)
Hydrogenation behavior of 4-isopropylphenol to 4-isopropylcyclohexanol over activated carbon-supported rhodium catalysts in supercritical carbon dioxide (scCO(2)) at 313 K was studied in a batch reactor and the results were compared with those in 2-propanol. Higher yields of cis-4-isopropylcyclohexanol were obtained in scCO(2) than in 2-propanol, and the formation of a byproduct, isopropylcyclohexane, was suppressed in scCO(2). The catalyst modification with hydrochloric or phosphoric acid enhanced the yield of cis-4-isopropylcyclohexanol in both scCO(2) and 2-propanol solvents. Kinetic analyses of the reaction profiles revealed higher reaction rates in scCO(2) than those in 2-propanol for the 4-isopropylcyclohexanol formation both by the direct hydrogenation of 4-isopropylphenol and by the consecutive hydrogenation of 4-isopropylcyclohexanone, and also revealed that the addition of hydrochloric acid increased the consecutive hydrogenation rate of 4-isopropylcyclohexanone to cis-4-isopropylcyclohexanol, which reduced the total reaction time needed for the complete hydrogenation of 4-isopropylphenol to 4-isopropylcyclohexanol.

Effect of carbon dioxide pressure on 4-t-butylphenol hydrogenation activity of supported rhodium catalyst - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of the Japan Petroleum Institute, 2013)
Hydrogenation of 4-t-butylphenol over an activated carbon-supported rhodium catalyst in carbon dioxide solvent was analyzed based on phase observation with a view cell and calculations of the solubility of 4-t-butylphenol using the Peng-Robinson equation of state as a function of carbon dioxide pressure. The reaction experiments showed that the initial reaction rate of 4-t-butylphenol at 313 K under 2 MPa of hydrogen pressure was increased by the addition of carbon dioxide, especially above a total pressure of 11 MPa. Direct visual observation showed that the solubility of 4-t-butylphenol increased with higher carbon dioxide pressure. The calculations based on the Peng-Robinson equation of state also showed that the solubility of 4-t-butylphenol in the 4-t-butylphenol carbon dioxide hydrogen (2 MPa) system at 313 K significantly increased by addition of carbon dioxide above a total pressure of 11 MPa. We concluded that the increase in the hydrogenation rates was caused by the increased concentration of 4-t-butylphenol substrate in the carbon dioxide solvent.
Keywords: 4-t-Butylphenol hydrogenation; Carbon dioxide solvent; Peng-Robinson equation; Rhodium catalyst; Supercritical fluid